Perspective: Can growth monitoring and promotion accurately diagnose or screen for inadequate growth of individual children? A critical review of the epidemiological foundations - Leroy, Jef L.; Brander, Rebecca L.; Frongillo, Edward A.; Larson, Leila M.; Ruel, Marie T.; Avula, Rasmi (Elsevier, 2025)
Growth monitoring and promotion (GMP), the process of periodic anthropometric measurements to assess the adequacy of individual child growth, is implemented across low- and middle-income countries (LMICs). The epidemiological foundations of GMP (i.e., that GMP can accurately diagnose or screen for inadequate growth) have never been critically reviewed. We first assessed growth patterns of individual healthy children. Using longitudinal data from low-, middle-, and high-income countries, we evaluated whether commonly used GMP criteria can be used for diagnosis and screening; i.e., if they accurately identify current, or predict subsequent, inadequate growth in individual children. The growth of individual healthy children does not track along a specific growth curve which challenges the notion that growth measurements alone can be used to distinguish between healthy and inadequate growth. We demonstrate that GMP criteria do not provide meaningful diagnostic information and that GMP is not a meaningful screening activity: commonly used GMP criteria are inaccurate predictors of (inadequate) growth later in childhood; and collecting individual children’s weight and height does not help to identify who needs support or who will benefit. Our results do not undermine the importance of dedicated programs to diagnose wasting in individual children nor do they challenge the need for well-child care to support parents and to ensure children’s optimal nutrition, health, and development. Our findings, however, highlight the need to carefully reconsider the current design of GMP in LMICs.